Managerial Pay (Cadrisme) and the Post Keynesian Growth Model - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2010)
This paper examines the effects of managerial pay on the Post Keynesian model of growth and distribution. Introducing managerial pay explains why economies may exhibit both wage- and profit-led characteristics in response to changed income distribution. Second, managerial pay undoes Pasinetti's (1961/2) theorem regarding the irrelevance of worker saving behavior for long run growth outcomes. Third, managerial pay links neo-classical Marxist theory with Post Keynesian growth theory. Neo-classical Marxists focus on why firms may choose inefficient production techniques. Similar logic carries over to Post Keynesian growth theory and firms may choose techniques that lower growth because they increase profits.
urn:nbn:de:101:1-201101312878
Keywords: E12; E25; O40; 330; Post Keynesian growth theory; managerial pay; neo-classical Marxism; Managervergütung; Postkeynesianismus; Wachstumstheorie; Verteilungstheorie; Neoklassik; Marxismus; Theorie